Psicanálise: ciência do singular - Wanderley Magno de Carvalho (2017)
This thesis addresses the scientificity of psychoanalysis and that which can characterize it as a science of the singular. It comprehends the work of the founder of psychoanalysis, Sigmund Freud, and of the French psychoanalysts Jacques Lacan and Jacques-Alain Miller, in a dialogue with the philosophical contributions of Martin Heidegger and Alain Badiou. It begins by a presentation of the existing definitions and conceptions concerning the sciences. It approaches Martin Heideggers critic of modern metaphysics, traced in its origins and extended to contemporaneity. From metaphysics one highlights its fundamental ontotheological traits and how they appear in Heideggers critic of modern sciences. Next, it resorts to the work of the contemporary philosopher Alain Badiou, his propositions regarding the mathematical theory of sets, his concepts of universal and singular, event and eventual site, as applied to the debate on sciences. A concept of science is then proposed. Afterwards, the results of an extensive research on Freuds conception of science are presented, along with the uses of the terms science and sciences throughout his work and the case he makes for psychoanalysis as a science. Based on bio-bibliographical notes from the founder of psychoanalysis and on Alain Badious concepts of subject and scientifical subject, Freud is portrayed as a subject true to both the scientifical truths and the defense of psychoanalysis scientificity. The final chapter deals with the notion of singular, as conceived by Lacan and further developed by Jacques Alain-Miller. A brief compilation of Lacans use of topology is brought forth, in order to identify the origins of the elaboration of the concept of sinthome. The last section consists in a thorough exam of the sinthome, such as formulated by Lacan in the Seminar 23 and referred in the following seminars. One concludes with a consideration on the initial hypothesis and the gathering of the points presented and debated throughout the research.